2020
DOI: 10.3389/fphar.2020.579525
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Beta-Blockers in Patients With Long QT Syndrome 1–3 According to Individuals’ Gender, Age, and QTc Intervals: A Network Meta-analysis

Abstract: Long QT syndrome (LQTS) is an arrhythmic heart disease caused by congenital genetic mutations, and results in increased occurrence rates of polymorphic ventricular tachyarrhythmias and sudden cardiac death (SCD). Clinical evidence from numerous previous studies suggested that beta blockers (BBs), including atenolol, propranolol, metoprolol, and nadolol, exhibit different efficacies for reducing the risk of cardiac events (CEs), such as syncope, arrest cardiac arrest (ACA), and SCD, in patients with LQTS. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
1
18
0
3
Order By: Relevance
“…The main limitation was that their recommendation was geared primarily toward female patients, given limited male patient data. These findings nonetheless were also supported by Saadeh , nadolol appears to be the ideal potential β-blocker of choice in all LQT subtypes, and atenolol followed by propranolol offers viable alternatives in types 1 [1,2,5,24].…”
Section: Role Of β-Blocker In Lqtssupporting
confidence: 56%
See 4 more Smart Citations
“…The main limitation was that their recommendation was geared primarily toward female patients, given limited male patient data. These findings nonetheless were also supported by Saadeh , nadolol appears to be the ideal potential β-blocker of choice in all LQT subtypes, and atenolol followed by propranolol offers viable alternatives in types 1 [1,2,5,24].…”
Section: Role Of β-Blocker In Lqtssupporting
confidence: 56%
“…Ahn et al supported the use and role of nadolol in risk reduction in LQT1 and LQT2 [ 1 ]. Han et al supported this; they focused heavily on the significant reduction in ACE in LQT1 and LQT2 by β-blockers, and the role of nadolol was seen as being ideal in both types, with atenolol a possible substitute in LQT1 [ 2 ]. Saadeh et al 2020 confirmed the role of β-blockers in LQTS as a whole and emphasized the efficacy and role of nadolol in LQTS 3, where previously β-blockers were thought to be contraindicated [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations